Human fetal osteoblast cell response to self-assembled nanostructures on YSZ-(110) single crystal substrates - Aminuddin, N.I.; Ahmad, Roslina; Ansari, H.M.; Mohd Zain, Norita; Akbar, S.A.; Pingguan-Murphy, Belinda (Elsevier, 2016)
In this study, self-assembled nanostructures on (110)-oriented yttria-stabilized zirconia single crystal substrates (YSZ-(110)) were utilized for a preliminary cell study using human fetal osteoblast (hFOB) cells. The bar-like nanostructures formed due to a morphological instability upon doping YSZ-(110) surfaces with 10 mol% gadolinium-doped ceria (GDC) at 1100 °C. The nanostructures were 62.9 ± 20.1 nm wide (on average) with an inter-bar spacing of 34.5 ± 6.8 nm. As part of the cell study, hFOB cell morphology, filopodia interaction, cell proliferation and viability on the nanostructures were studied and compared with the standard tissue-culture treated slips. More cells were observed on the nanostructured surfaces and cell proliferation assay results suggested that the cells preferred the nanostructured surfaces compared to the smooth slips. The nanostructures increased YSZ-(110) surface roughness and improved its wettability which consequently increased cell adhesion and subsequent proliferation. The results also indicated that hFOB cells liked the nanoscale environment and thrived on the nanostructures, which were smaller than the dimension of natural extracellular matrix (ECM).